2017
DOI: 10.7150/ijbs.16818
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Inhibits Glioblastoma Stem-like cells through Suppression of EZH2-NOTCH1 Signaling Axis

Abstract: Glioblastoma stem-like cells (GSCs) play essential roles in glioma growth, radio- and chemo-resistance, and recurrence. Elimination of GSCs has therefore become a key strategy and challenge in glioblastoma therapy. Here, we show that melatonin, an indolamine derived from I-tryptophan, significantly inhibited viability and self-renewal ability of GSCs accompanied by a decrease of stem cell markers. We have identified EZH2-NOTCH1 signaling as the key signal pathway that regulated the effects of melatonin in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 30 publications
(30 reference statements)
3
42
0
1
Order By: Relevance
“…Melatonin (N‐acetyl‐5‐methoxytryptamine), a circardian and circannual cycle regulator, was also known to have antioxidant, anti‐inflammatory, and antitumor effects in various cancers such as brain, lung, breast, prostate, leukemia, colon, and liver cancers. Recently, melatonin was reported to suppress the growth of glioblastoma stem cells via inhibition of EZH2‐Notch1 or Akt‐EZH2‐Stat3 signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin (N‐acetyl‐5‐methoxytryptamine), a circardian and circannual cycle regulator, was also known to have antioxidant, anti‐inflammatory, and antitumor effects in various cancers such as brain, lung, breast, prostate, leukemia, colon, and liver cancers. Recently, melatonin was reported to suppress the growth of glioblastoma stem cells via inhibition of EZH2‐Notch1 or Akt‐EZH2‐Stat3 signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin has been shown to inhibit proliferation of many types of cancer cells such as glioblastoma cells, colon cancer cells, and breast cancer cells (49)(50)(51). Melatonin exerts its anti-proliferative activity by inactivating FoxO-1 and NF-κB transcription factors, downregulating myosin light chain kinase expression through cross-talk with p38 MAPK, or by suppressing Notch1 signaling (49,52,53). It remains to be tested whether melatonin is involved in goblet cell differentiation by regulating Notch1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin, which is synthesized from tryptophan by enzymes N-acetyltransferase and acetylserotonin methyltransferase, is produced in many tissues, including the gastrointestinal tract as well as in the pineal gland (47,48). Melatonin has been shown to inhibit proliferation of many types of cancer cells such as glioblastoma cells, colon cancer cells, and breast cancer cells (49)(50)(51). Melatonin exerts its anti-proliferative activity by inactivating FoxO-1 and NF-κB transcription factors, downregulating myosin light chain kinase expression through cross-talk with p38 MAPK, or by suppressing Notch1 signaling (49,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2) may in part explain the inhibitory effect of melatonin on GSCs. Zheng et al [85], studying the knockdown of EZH2 in GBM cells, observed a significant downregulation of Notch1, a transmembrane protein with an important role in cell embryonic and postnatal development [85][86][87][88] that is overexpressed in many cancer types, like breast, lung, pancreatic, and colon cancer [88]. The depletion of EZH2 also reduced the quantity and self-renewal activity of GSCs.…”
Section: In Vitro Evidence Of Melatonin Effects Against Glioblastomamentioning
confidence: 99%